Enhancing Reading Proficiency with the Call-Up Approach - Cadorna, Nechor Talaroc (Lumbini Journal of Language and Literature, 2026)
This study aimed to enhance the reading proficiency of Grade 7 learners at San Pedro Integrated School through the CALL UP Approach, a tutorial-based intervention. Specifically, the objective was to improve students’ English performance by targeting vocabulary, comprehension, and reading fluency using structured weekly sessions and individualized support. The method used was both a quasi-experimental design and an extension program implemented in partnership with the Department of Education. The extension program was conducted over four weeks and included a pre- test and post-test assessment, monitoring of affective filters, tutor observations, and structured tutorial sessions designed based on DepEd-aligned competencies and the Call Up Approach. The study found that the students’ reading proficiency level prior to the intervention ranged from ‘poor’ to ‘satisfactory’, as reflected in the concentration of scores on the self-made diagnostic test. Weekly monitoring of affective filters revealed fluctuating results alternating from ‘mixed’ to ‘positive’ which may be attributed to the weekly rotation of tutors. Nevertheless, the students' reading levels remained consistently within the instructional level across all four tools administered. Similarly, positive washback was observed consistently throughout the four reading sessions, as evidenced by student engagement and progression. Tutors consistently rated overall student performance as ‘good’. Post-test results showed noticeable improvement, ranging from less to high development in reading proficiency after the intervention. Based on the findings, it is recommended that the next phase of the intervention include enhanced instructional materials focusing on assessing prior knowledge and making inferences, the two areas where development was limited. Further, the tutorial delivery system should be re-evaluated to ensure consistency in affective learning conditions. This study underscores the potential of extension programs such as the Call Up Approach to contribute meaningfully to educational recovery, particularly in strengthening English proficiency among junior high school students.